Quaderna: a lírica erótico-amorosa de João Cabral de Melo Neto - Marques, Patrícia (2010)
The following essay is aimed to reflect the poems from the book Quaderna (1960), by the poet João Cabral de Melo Neto. Its focus is to reflect on the tension knot that generates a reversal lyricism from the traditional lyricism. In order to reach this goal, the following questioning is raised: To what extent, does the book Quaderna, materializes a lyric-erotic-loving voice in the poetic of João Cabral de Melo Neto? The theoric reason that guides this paper is composed by two strands, the first one on theoric that tried to apprehend in theories such as Hugo Friedrich s and Käte Hambruger s, the lyricism type registered in Quaderna, the second strand looked for in João Cabral´s criticism the possibilities of female thematization through a loving-erotic vein. The paper tries to explore, throughout three chapters, the poems imagery wealth,outstanding primarily the poetic width of Cabralian speech, that concerns the visuality,plasticity,concretion and sensuousness. Among other considerations, it´s aprehended in Quaderna the love-lyricism thematic that emphasizes the female through a sensual erotic language that creates the similarities between the woman and the natural elements, besides it also prioritizes the poetic writing as a lyricism